Fuel load and flight ranges of blackcaps Sylvia atricapilla in northern Iberia during autumn and spring migrations - JUAN ARIZAGA, EMILIO BARBA (Current Zoology, 2009)
Fuel accumulation, mainly as fatty acids, is one of the main characteristics of migratory birds. Studying to what extent each population or species manages fuel load and how it varies along routes of migration or between seasons (autumn and spring migrations) is crucial to our understanding of bird migration strategies. Our aim here was to analyse whether migratory blackcaps Sylvia atricapilla passing through northern Iberia differ in their mean fuel loads, rate of fuel accumulation and 'potential' flight ranges between migration seasons. Blackcaps were mist netted for 4 h-periods beginning at dawn from 16 September to 15 November 2003–2005, and from 1 March to 30 April 2004–2006 in a European Atlantic hedgerow at Loza, northern Iberia. Both fuel load and fuel deposition rate (this latter assessed with difference in body mass of within-season recaptured individuals) were higher in autumn than in spring. Possible hypotheses explaining these results could be seasonal-associated variations in food availability (likely lower during spring than during autumn), the fact that a fraction of the migrants captured in spring could breed close to the study area and different selective pressures for breeding and wintering [Current Zoology 55 (6): 401–410, 2009].